Urgensi Pembaharuan Hukum di Era“Metaverse” dalam Perspektif Hukum Progresif - Ambarwati, Dewi (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2022)
Metaverse is the latest technology issue widely discussed, especially during a pandemic that limits humans from massive physical gatherings. In the Metaverse world, users can transact virtually and carry out economic, entertainment, and social activities. This is where the urgency of law reform in the economic field arises, which aims to accommodate the community's needs and is an instrument to protect rights and obligations. In addition, researchers will examine and describe normatively and conceptually what business aspects can be done in the metaverse and the urgency of legal reform for metaverse users who transact virtually. This research is normative juridical research using statutory and conceptual approaches. The legal materials used are secondary and analyzed descriptively and qualitatively. The results of the study found that various business potentials can be carried out in the metaverse world, including several legal aspects. From the many opportunities and challenges that exist in the metaverse world, progressive legal norms are needed to provide legal protection for the community by formulating a legal product (law or implementing regulation) that is integrated with all digital aspects that can be used specifically for managing virtual transactions in the metaverse world.